Arquitectura Informática para Geo Localización de Medicamentos en Farmacias. - Caraguay Caraguay, Leonardo Favio (2020)
In the present work of qualification, the development of a computer architecture is written, whose main objective is to optimize the search and location of medicines in the different pharmacies, in addition to knowing if the pharmacy is open through two mobile applications and a web service or web service The first mobile application aimed at customers of pharmacies where it allows them to search for medications and know necessary information about them such as their location and availability among others, the second mobile application aimed at pharmacies that allows interaction with the client through consultations in real time knowing the details of the drug sought by the client and allowing to issue a response to these queries and finally the web service responsible for managing the data and all the interactivity between mobile applications. The development of this degree work was divided into three goals such as the definition of architecture, development and testing of it. In the first instance, a review of the literature was necessary with topics related to computer architectures, types of software, mobile applications, development frameworks, maps, databases, web service and development methodologies, then in the development section tables were made comparisons where the appropriate architecture for the project was defined, resulting in two mobile applications in the ionic framework connected through a web server developed with GraphQL technology, all this developed according to the Mobile-D methodology. Then, based on the selected methodology, the architecture design was carried out, which includes the lifting of requirements based on the techniques defined in the materials and methods section. Surveys and interviews are used to obtain the necessary information and the IEEE Std standard was used. 830-1998 to better handle this information. The development of mobile applications and the web service based on various development tools was carried out. Finally, the respective tests were carried out for this, a simulated environment was defined where students of the systems engineering career of the National University of Loja were used as the selected population, all the tests were based on the IEEE 829 standard that is aimed at software tests, resulting in a positive balance of success in the tests performed.